Penyedap Rasa Sere Kedele dengan Penambahan Pediococcus acilactici strain SKS 251 pada Saat Fermentasi Ditinjau dari SNI 01-4273-1996 dan Sifat Sensoris - Wipradnyadewi, Putu Ari Sandhi; Sugitha, I Made; Wayan Gunam, Ida Bagus; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPA, 2025)
Sere kedele is a fermented food made from soybeans which is widely available in Gianyar and Klungkung Regencies. The use of food additives (BTP) in food and drinks is often found.  One of them is flavoring. The aim of this research is to determine the flavoring of sere kedele with the addition of Pediococcus acilactici strain SKS 251 during fermentation in terms of SNI 01-4273-1996 and sensory properties. In this study, the water content, protein content, glutamic acid content, total microbes, NaCl content, total yeast mold, coliform flavoring of sere kedele were observed in accordance with SNI 01-4273-1996 and sensory properties including color (level of color and preference), aroma , taste (level of pleasantness and liking) and overall acceptability (level of liking). The results of the research showed that sere kedele flavoring had a water content of 4.62%, protein content of 6.75%, NaCl content of 0.74%, glutamic acid of 0.47%, total yeast mold of 8.8x103 CFU/g total microbes 7, 7x104 CFU/g and total coliform <3 APM/g, the average value for the level of clarity and the level of preference for color is 5 and 5.27, the value for aroma is 6, the level of savoriness and the level of preference for taste are 6.20 and 6, 33 and the average value for the level of liking for overall acceptance is 6.40 on a scale of 0 to 10.Further research is needed on the potential of sere kedele as a flavoring in accordance with SNI 01-4273-1996 concerning powdered broth flavorings. Key words: sere kedele , flavoring, SNI 01-4273-1996, sensory properties